Review on collect of Luther’s works «On the Babylonian Captivity of the Church» edited by Ivan Fokin (Saint-Petersburg, 2017) - Rodion Valentinovich Savinov (Религия, церковь, общество, 2018)
The author considers the collection of Martin Luther’s works, edited by Ivan Fokin, timed to the 500th anniversary of the Reformation. The review included description of the collection, and analysis of key texts from each section. An evaluation of this edition is suggested in the context of Russian research literature devoted to the Reformation and the early Modern.